2018
DOI: 10.1504/ijnt.2018.098434
|View full text |Cite
|
Sign up to set email alerts
|

Caesium and strontium adsorption ability of activated bamboo charcoal

Abstract: We developed an activated charcoal by creating bamboo charcoal that was carbonised at a temperature between 400 to 1000°C and then kept it at a temperature of 270°C for 2 h. One gram of activated charcoal was added to 100 mL of aqueous caesium of 2.67 × 10-2 mmol/L and 100 mL of strontium aqueous solution, and was stirred for 1 h. The caesium adsorption amount of bamboo charcoal, which was carbonised at 400°C, increased from 70.0% to 88.9%. In addition, the amount of strontium absorbed increased from 76.5%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, sorption processes have retained much more attention, playing with a wide diversity of supports. Carbon-based sorbents have been investigated for Sr(II) uptake from surface waters [10][11][12][13]. Biosorbents and biopolymers showed also promising properties for strontium uptake.…”
Section: Introductionmentioning
confidence: 99%
“…However, sorption processes have retained much more attention, playing with a wide diversity of supports. Carbon-based sorbents have been investigated for Sr(II) uptake from surface waters [10][11][12][13]. Biosorbents and biopolymers showed also promising properties for strontium uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Many biosorbents have been tested for Sr(II) recovery from dilute solutions, including moss [7], bacteria [15], yeast [16], fishbone [17], algal biomass [18,19], biopolymers [20,21]. Carbon-based sorbents were also used for Sr(II) removal from aqueous solutions [22,23,24,25]. Mineral sorbents, such as clays [6,26,27], silica, and titanate, have retained great attention under their raw form or after impregnation with extractants [28,29], or after immobilization of solid ion-exchangers [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…They found that this AC shows a maximum adsorption capacity of 13.58 mg g −1 when the activation temperature, pH level and initial adsorbate concentration are 400 • C, pH 6 and 70 mg L −1 , respectively. In 2018, Hayakawa et al [28] studied strontium removal using bamboo-based activated carbon. AC showed a maximum adsorption capacity of 32.62 mg g −1 when the activation temperature, pH level and initial adsorbate concentration were 800 • C, pH 9.5 and 10 mg/L, respectively.…”
Section: Surface Properties and Adsorption Capacity Of Biomass-derive...mentioning
confidence: 99%
“…These low-cost locally available biomass/biomass wastes ensure the cost-effective manufacturing of activated carbon, and they also provide higher quality and enhanced adsorption performances [26]. Among biomass sources, rice husks [27], bamboo [28], sugarcane bagasse [29], potato peels [30], coconut shells [31], waste palm trunks [32][33][34] and mangrove woods [35][36][37] are rich in carbon content and hence can be used for the synthesis of activated carbon. These biomass sources are readily available in most countries, such as Bangladesh, and are also very effective for removing the concerned radionuclides.…”
Section: Introductionmentioning
confidence: 99%